2001
DOI: 10.1002/1097-4652(2001)9999:9999<000::aid-jcp1038>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Altered macrophage-like functions of preadipocytes in inflammation and genetic obesity

Abstract: We recently demonstrated that preadipocytes exhibit functional features of macrophages, such as phagocytosis and anti-microbial activity, suggesting that preadipose cells could play a role in the inflammatory process or immune response. The aim of this study was to compare these functions of both macrophages and cells from stroma-vascular fraction (SVF) of the adipose tissue in two different situations, obesity and inflammation, characterized by alterations in immune responsiveness. We demonstrated that ob/ob … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 29 publications
3
51
1
2
Order By: Relevance
“…For example, it has been postulated that macrophages resident in adipose tissue contribute to obesity-associated inflammation and insulin resistance [4,5]. Furthermore, it has been shown that preadipocytes/SVC can function as macrophage-like cells and may play a direct role in inflammation response and obesity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been postulated that macrophages resident in adipose tissue contribute to obesity-associated inflammation and insulin resistance [4,5]. Furthermore, it has been shown that preadipocytes/SVC can function as macrophage-like cells and may play a direct role in inflammation response and obesity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These have been implicated in the pathogenesis of insulin resistance and cardiovascular disease (3,4,6,11). Recent studies have shown that obese adipose tissue exhibits increased infiltration by macrophages and, moreover, that macrophages may be a primary source of proinflammatory factors (12)(13)(14)(15)(16). Thus, macrophage infiltration into adipose tissue may be an important contributor to the enhanced inflammatory activity in obesity.…”
mentioning
confidence: 99%
“…[7][8][9] Macrophages have been observed in crown-like structures aggregating around adipocytes. 10,11 Furthermore, a correlation between adipocyte size or fat mass and macrophage marker expression has been found in adipose depots of different murine models of obesity.…”
mentioning
confidence: 99%